Penerapan Arsitektur Metafora Pada Perancangan Sekolah Tinggi Penerbangan Di Kulon Progo Yogyakarta - Anindya Nurryan Iskandar; Anggraeni Dyah Sulistiowati (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
Aviation high school is an educational institution tasked with preparing transportation human resources through education and training channels and its function is to carry out education, training, research and community service in the field of air transportation. Metaphoric architecture is the concept of development of a form of object taken and developed in a building.Keywords: Banten Creative Hub, Contemporary Architecture